Region-specific rnhancement of c-fos expression by combined treatment with NMDA receptor agonists and antagonists with antidepressant potential: brief report - Vasilescu, Andrei-Nicolae; Pfeiffer, Natascha; Terraneo, Federica; Riva, Marco Andrea; Lang, Undine E; Inta, Dragos; Gass, Peter (The international journal of neuropsychopharmacology, 2022)
Rapastinel, formerly Glyx-13, is a novel positive allosteric modulator of the N-methyl-D-aspartate-receptor (NMDAR) that counteracts psychotomimetic actions of NMDAR antagonists. We set out to evaluate the effect of rapastinel alone or in combination with the global and GluN2B subunit-specific NMDAR antagonists MK-801 and Ro25-6981, respectively, on neuronal activation in relevant regions using c-fos brain mapping. Whereas rapastinel alone did not trigger significant c-fos expression beyond the prelimbic cortex, it strongly increased the c-fos expression induced by MK-801 in hippocampal, cingulate, and retrosplenial areas. Similar results were obtained when rapastinel was replaced by D-cycloserine. Our results reveal new interactions at network level between NMDAR modulators with possible implications regarding their therapeutic effects.